Caribbean islands 2024 - Egerton, Alex (Lonely Planet guidebooks., 2023)
Lonely Planet's Caribbean Islands is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Set sail from Tortola, snorkel in Aruba's clear waters, and feel the music in Cuba; all with your trusted travel companion.